Studying the QCD medium in proton-proton collisions using PYTHIA - Elsherif, Omar Tarek (AUC Knowledge Fountain, 2018)
It is believed that in the first microsecond after the big bang, the universe was in a state known as the Quark-Gluon Plasma (QGP), where quarks and gluons were asymptotically free. Signatures of QGP like jet quenching and elliptic flow have been observed in heavy-ion collisions at RHIC and LHC experiments. The aim of this study was to investigate the possibility of QGP formation in proton-proton (p-p) collisions. PYTHIA was used to simulate the p-p collision at center-of-mass energies of âˆšs = 200 GeV and âˆšs = 13 TeV corresponding to the available energies of the current collider experiments. The ratios between the near-side and away-side yields associated with the high transverse momentum particles were calculated and compared for the low and high multiplicity events as a function of transverse momentum in order to search for such phase. For LHC energies at high multiplicity, away-side yields show suppression in comparison to near-side yields. This indicates that there is a possibility of creating QGP at high-energy high-multiplicity p-p collisions.